The Digital Euro Project. A Preliminary Assessment - Iulia Monica Oehler-Şincai (Romanian Journal of European Affairs, 2022)
The decrease in physical cash usage, the excessive market power of BigTech companies, the largely unregulated market of crypto assets which poses risks to financial stability, as well as the need for more financial inclusion and for lower-cost crossborder payments are just as many arguments in favour of a central bank digital currency (CBDC). However, there are as many points urging caution. In this context, the purpose of the present paper is to analyse the specificity of the potential digital euro as part of the international payments’ architecture. The European Central Bank (ECB) is focusing on the digital euro project, running the investigation phase until October 2023. The debate on the digital euro adoption is in line with the international one, but there are several distinctive aspects. Various scenarios are taken into account, starting from general principles for retail CBDCs, results of the public consultation of a digital euro, experts’ opinions regarding privacy, security, usability, costs, offline use, acceptance, potential disintermediation, standards and international implications of the digital euro. The research also outlines the relations between major actors involved, while identifying the prerequisites for a swift functioning of the Eurozone payment system with digital euro at its core.